Problem tyranii w radykalnej myśli prezbiteriańskiej. Przypadek Samuela Rutherforda - Tulejski , Tomasz (Studia Europaea Gnesnensia, 2019)
The article delves into the principles of the right to resistance in radical Presbyterian thought. As an example, the author discusses Samuel Rutherford’s political theology, which represents a consummation of the earlier concepts of tyranny and right to disobey that had been formulated largely within the Calvinistic camp. The theology in question became one of the chief arguments in support of the Puritan Revolution in England.